Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Bagian Kunci Pintu Merek Dekkson Di Toko Depo Makmur Sorong - Mahyudin Tuasikal; Dukayom Latuamuri; Sarah Makdalena Yable (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
In the era of globalization, today's business competition is getting tougher, which requires business actors to be able to survive and compete with other business competitors, either similar businesses or other businesses that are rife in today's global market. One of the efforts that can be made by business actors is by improving product quality and service quality in their business. Because service quality is an important factor in increasing competitiveness in business.